Efektivitas pelatihan kerja terhadap kinerja kader Posyandu - Ni Made Darmiyanti Darmiyanti; Ni Wayan Ari Adiputri (Jurnal Kebidanan, 2020)
The number of Posyandu throughout Indonesia reaches 202,676 Posyandu, in Bali 4,791 Posyandu and Karangasem Regency 555 Posyandu, while in Manggis Village, there are 12 Posyandu. The level of utilization of Posyandu nationally in 2010 only reached 50.5%, where there was a 12% decrease in the utilization of Posyandu until 2015. This should be in past tense the effectiveness of job training on Posyandu cadre's performance in Manggis Village, Manggis District, Karangasem Regency in 2018. The study was conducted with a quasi-experiment research design with the design pre-test post-test method. The research subjects used 60 Posyandu cadre in the Manggis Village area. The analysis used the Wilxocon Sign Rank Test with a confidence level of 0.05. The results showed that the value of p = 0.00 <0.05, so that the job training given to Posyandu cadre had a significant effect on improving Posyandu cadre's performance.